Covidorthodontics: the new normal - Chawla, Riddhi; Malik, Robin (Orthodontic Journal of Nepal, 2020)
The purpose of this review article is to summarize the contingency management guidelines of major orthodontic procedures to enable us set new norms for orthodontics keeping in mind the implications of the prevailing pandemic. Studies on efficacy of stringent infection control during COVID 19 era for orthodontic procedures published in 2020 were retrieved from various databases like COVID 19 Open Research Dataset, PubMed, MEDLINE, Scopus and Google Scholar. Thus, considering the unreliability and the worrisome environment of this COVID era it is evident that clear guidelines are required for defining orthodontic emergencies, prioritizing COVID 19 testing and PPE requirements for orthodontists and secure virtual consultation platforms. It’s extremely mandatory for us to evolve with the ever evolving world and successfully strive together as a community maintaining our patients trust as well as the standard of orthodontic care being offered by us. This unity amongst us and balance of our duties need to become part of our daily lives and be adopted as a new normal.